PENGARUH KONTROL SOSIAL DAN KESADARAN HUKUM TERHADAP PATOLOGI SOSIAL REMAJA DI PERKOTAAN: PERSPEKTIF SOSIOLOGI HUKUM - Fero Sanjaya; Muhammad Zaky Nugraha; Wevy Efticha Sary (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Social pathology among adolescents has become an increasingly prominent issue in urban areas, posing serious challenges to social order and legal effectiveness. This study aims to analyze the influence of social control and legal awareness on adolescent social pathology in urban settings from a sociology of law perspective. The research employed a quantitative approach with an explanatory correlational design. Data were collected through a structured questionnaire using a Likert scale, distributed to 200 high school students selected through stratified random sampling. The research instruments were tested for validity and reliability prior to data analysis. Multiple linear regression analysis was conducted using SPSS software. The results indicate that social control has a negative and significant effect on adolescent social pathology. In addition, legal awareness also shows a negative and significant influence on social pathology among adolescents. Simultaneously, both variables significantly explain variations in deviant behavior among urban adolescents. These findings suggest that stronger social control mechanisms and higher levels of legal awareness contribute to reducing social pathology among youth. This study contributes to the development of sociology of law by emphasizing the role of law as an effective mechanism of social control when supported by strong social structures. Practically, the findings provide empirical evidence for policymakers, educational institutions, and social agencies to design preventive strategies focusing on strengthening social control and enhancing legal awareness among adolescents in urban environments.